VD_FINDINFO HC / 2015 / 621 vom 18. August 2015 - VD Tribunal cantonal (2015)
CONTRAT DE TRAVAIL, RÉSILIATION IMMÉDIATE, JUSTE MOTIF, FAUX DANS LES CERTIFICATS | 337 al. 1 CO, 337 al. 2 CO, 337 al. 3 CO, 337 CO